TRIzol-based RNA extraction for detection protocol for SARS-CoV-2 of coronavirus disease 2019. (May 2021) - Amirouche, A.; Ait-Ali, D.; Nouri, H.; Boudrahme-Hannou, L.; Tliba, S.; Ghidouche, A.; Bitam, I.
Abstract: Diagnostic testing is important for managing the 2019 novel coronavirus (SARS-CoV-2). We developed an optimized protocol for SARS-CoV-2 RNA extraction from the surface of the respiratory mucosa with nasopharyngeal swabs and compared the sensitivity of RNA extraction methods. RNA extraction was performed using three different procedures (TRIzol, QIAamp, VMT-TRIzol) from nine positive SARS-CoV-2 samples. SARS-CoV-2 was detected by real-time reverse transcriptase PCR (RT-PCR) using a detection kit for SARS-CoV-2 (Sun Yat-sen University). Compared to RT-PCR results, there were no discernible differences in detection rates when comparing the three different extraction procedures. On the basis of these results, the use of TRIzol as a transport medium and RNA extraction method for SARS-CoV-2 detection may be a helpful alternative for laboratories facing shortages of commercial testing kits.